Locating the Social in Social Justice. Issue 2 (4th March 2018) - Lake, Robert W.
Abstract : A concept of social justice in which the social names a subset of justice suggests that the social constitutes a distinct sphere within which a distinctively social justice is produced and experienced and within which a specifically social injustice can be addressed. Theorists from Dewey to Latour to Foucault, however, have questioned the conceptualization of the social as a separate substantive domain within which a distinctively social justice can be found. I seek to move from a substantive to a relational conceptualization of the social in social justice, drawing from Dewey's concept of the social as an associative rather than an aggregative relation. A relational approach situates the social not in a delimited substantive domain within which justice can be assessed but as a mode of collective association through which justice is performed and produced. Relocating the social from a substantive sphere to a relational practice transforms the problem of social justice. Rather than assessing the justice of outcomes within a specifically social sphere, the problem of social justice addresses the interactive practices of social actors engaged in the collective project within which justice is dialectically and simultaneously a process and an outcome, a means and an end. I illustrate the challenges of practicing a relational conception of social justice in an antidisplacement protest against a neighborhood redevelopment proposal in Camden, New Jersey. The case study suggests that furthering the goal of social justice focuses on everyday practices of associative interaction in which relations of democratic equality are undermined or encouraged.